The Pseudo-Democrat's Dilemma Why Election Observation Became an International Norm - Hyde, Susan D. (Cornell University Press, 2011)
Cowinner of the International Studies Association's Chadwick F. Alger Prize, Winner of the American Political Science Association's Comparative Democratization Section Best Book Award, and Cowinner of the Yale University MacMillan Center's Gustav Ranis International Book Prize.Why did election monitoring become an international norm? Why do "pseudo-democrats" (undemocratic leaders who present themselves as democratic) invite international observers, even when they are likely to be caught manipulating elections? Is election observation an effective tool of democracy promotion, or is it simply a way to legitimize electoral autocracies? This book uses cross-national data on election observations since 1960 and case studies of Armenia, Indonesia, Haiti, Peru, Togo, and Zimbabwe to explain international election monitoring with a new theory of international norms.